Uncovering collaborative value creation patterns and establishing corresponding customer roles - MOELLER, Sabine (Institutional Knowledge at Singapore Management University, 2013)
Research on value creation traditionally has focused on value created by the company, though customers increasingly serve as active partners, able to create value with firms in a collaborative manner. Despite interest by both scholars and managers, existing research has not yet clarified the interdependencies of service offerings and customer role patterns. This article explores value creation rooted in three generic offerings (configuration, solution, and network) and identifies differences in their prerequisites, customer activities, challenges, abilities, ability enhancers, and perceived benefits that arise in collaborative value creation (CVC). Data from 105 collaborations, collected through in-depth interviews, support the qualitative and quantitative analyses that reveal distinct patterns in customers’ value creation for each service offering. A categorical principal components analysis, combined with cluster analysis, identifies five customer roles: bargain-hunting independent, comprehensive help seeker, engaged problem solver, technology-savvy networker, and self-reliant customizer. Our theoretical contribution includes the identification of customer roles across generic offerings and empirical evidence that customers perform multiple roles when engaging in CVC processes. Our findings provide managers engaged in CVC with recommendations on criteria for segmenting customer groups, on the role of the service provider in various value creation processes, and on tailored communication strategies to attract customers.